Predation by invasive rainbow trout on the critically endangered Pehuenche spiny‐chest frog. Issue 3 (21st December 2020) - Zarco, Agustín; Corbalán, Valeria; Debandi, Guillermo
Abstract: The Pehuenche spiny‐chest frog Alsodes pehuenche is an endemic species from the Andes of Argentina and Chile and is considered to be critically endangered. Its population has been declining over the past 10 years, principally as a consequence of the paving of a road that crosses the streams the frog inhabits. Until recently, exotic fish species had not been recorded in these streams. This study documents the presence of rainbow trout ( Oncorhynchus mikyss ) in one of these streams and predation on the endangered frog species.